THE ANALYZE EFFECT OF THE MOTIVATION, COMPETENCE, TASK ATTRACTIONS AND SITUATIONAL FACTORS OF PERFORMANCE SEKRETARIAT DAERAH EMPLOYEES PEMERINTAH KABUPATEN BIREUEN - Juli, Nova; Gusandra Saragih, Megasari (JURNAL KEBANGSAAN, 2016)
This research aims to identify the effect of the motivation, competence, task attractions and situational factors of performance Sekretariat Daerah Employees Pemerintah Kabupaten Bireuen. The samples in this study were 158 Sekretariat Daerah Employees Pemerintah Kabupaten Bireuen. The analytical tool used Structural Equation Modeling (SEM) using AMOS device-20 (Analysis of Moment Structure). The results showed that the motivation, competence, task attractiveness and situational factors has a positive and significantly effect to performance Sekretariat Daerah Employees Pemerintah Kabupaten Bireuen. Keywords: Motivation, Competence, Task Attractiveness, Situational Factors, Performance.